Vous êtes sur la page 1sur 97

7.1 The Logarithm Defined as an Integral

7.1 The Logarithm Defined as an Integral

What are logarithms?

log a b = x a x = b

What are logarithms? log a b = x ⇒ a x = b

What are logarithms?

log a b = x a x = b

a = ln x e a = x

What are logarithms? log a b = x ⇒ a x = b a = ln

What are logarithms?

log a b = x a x = b

a = ln x e a = x

ln x = x

1

1

t

dt,x > 0

are logarithms? log a b = x ⇒ a x = b a = ln x

What are logarithms?

log a b = x a x = b

a = ln x e a = x

ln x = x

1

1

t

dt,x > 0

What this last one means is that we can get the value for ln x by finding the area under the curve 1 to x.

> 0 What this last one means is that we can get the value for ln

The logarithm as an integral

Notice that the definition starts at 1. If you want ln x for 0 < x < 1 then the area is negative since ln x is negative there.

starts at 1. If you want ln x for 0 < x < 1 then the

The logarithm as an integral

Notice that the definition starts at 1. If you want ln x for 0 < x < 1 then the area is negative since ln x is negative there.

In this way we can define the number e.

ln e = e

1

1

t

dt

the area is negative since ln x is negative there. In this way we can define

The Graph

ln x crosses the x-axis at

The Graph ln x crosses the x -axis at

The Graph

ln x crosses the x-axis at (1, 0).

The Graph ln x crosses the x -axis at ( 1, 0 ) .

The Graph

ln x crosses the x-axis at (1, 0). The domain is

The Graph ln x crosses the x -axis at ( 1, 0 ) . The domain

The Graph

ln x crosses the x-axis at (1, 0). The domain is (0, ).

The Graph ln x crosses the x -axis at ( 1, 0 ) . The domain

The Graph

ln x crosses the x-axis at (1, 0). The domain is (0, ). lim + ln x =

x0

The Graph ln x crosses the x -axis at ( 1, 0 ) . The domain

The Graph

ln x crosses the x-axis at (1, 0). The domain is (0, ). lim + ln x =

x0

The Graph ln x crosses the x -axis at ( 1, 0 ) . The domain

The Graph

ln x crosses the x-axis at (1, 0).

The domain is (0, ).

lim + ln x =

x0

x ln x =

lim

the x -axis at ( 1, 0 ) . The domain is ( 0, ∞ )

The Graph

ln x crosses the x-axis at (1, 0).

The domain is (0, ).

lim + ln x =

x0

x ln x =

lim

x -axis at ( 1, 0 ) . The domain is ( 0, ∞ ) .

The Graph

ln x crosses the x-axis at (1, 0).

The domain is (0, ).

lim + ln x =

x0

x ln x =

lim

x 1 > 0 ln x is increasing.

∞ ) . lim + ln x = − ∞ x → 0 x → ∞

The Graph

ln x crosses the x-axis at (1, 0).

The domain is (0, ).

lim + ln x =

x0

x ln x =

lim

x 1 > 0 ln x is increasing.

1

2 < 0 ln x is concave down.

x

∞ ln x = ∞ lim x 1 > 0 ⇒ ln x is increasing. −

The Graph

The Graph

How this relates to the FTC

Remember, from the second part of the Fundamental Theorem of Calculus,

d

1

dx x t

1

dt = 1

x

relates to the FTC Remember, from the second part of the Fundamental Theorem of Calculus, d

How this relates to the FTC

Remember, from the second part of the Fundamental Theorem of Calculus,

So, dx ln x = x for x = 0.

d

1

d

1

dx x t

1

dt = 1

x

part of the Fundamental Theorem of Calculus, So, d x ln x = x for x

How this relates to the FTC

Remember, from the second part of the Fundamental Theorem of Calculus,

So, dx ln x = x for x = 0.

d

1

We can generalize this:

d

dx

d

dx

x

1

1

t

dt = 1

x

dy

ln u = 1

u dx

for x = 0. d 1 We can generalize this: d d x d d x

Justification

d

Where does dx ln x come from? Consider

e lnx = x

dx d e ln x =

d

dx x

Justification d Where does d x ln x come from? Consider e l n x =

Justification

d

Where does dx ln x come from? Consider

e lnx = x

dx d e ln x =

d

dx x

By applying the chain rule we get

dx d e ln x =

d

dx x

n x = x ⇒ d x d e ln x = d d x x

Justification

d

Where does dx ln x come from? Consider

e lnx = x

dx d e ln x =

d

dx x

By applying the chain rule we get

d

d

dx e ln x = dx x e ln x ·

d

dx ln x = 1

d d x x By applying the chain rule we get d d d x e

Justification

d

Where does dx ln x come from? Consider

e lnx = x

d

dx e ln x =

d

dx x

By applying the chain rule we get

d

d

dx e ln x = dx x e ln x ·

d

dx ln x = 1

1 ⇒ d ln x = = 1 dx e ln x x
1
⇒ d
ln x =
= 1
dx
e ln x
x

Generalization

And, in general, we have

d

dx

log b x =

Generalization And, in general, we have d d x log b x =

Generalization

And, in general, we have

d

dx

log b x =

1

x ln b

Generalization And, in general, we have d d x log b x = 1 x ln

Generalization

And, in general, we have

d

dx

log b x =

1

x ln b

And if we have a composite function u, we’d get

d

dx

log b u =

we have d d x log b x = 1 x ln b And if we

Generalization

And, in general, we have

d

dx

log b x =

1

x ln b

And if we have a composite function u, we’d get

d

dx

log b u =

1

1

ln b ·

u ·

x log b x = 1 x ln b And if we have a composite function

Generalization

And, in general, we have

d

dx

log b x =

1

x ln b

And if we have a composite function u, we’d get

d

dx

log b u =

1

ln b · u

1

· du

dx

x = 1 x ln b And if we have a composite function u , we’d

Properties

Other logarithm properties:

1 ln bx = ln b + ln x

Properties Other logarithm properties: 1 ln bx = ln b + ln x

Properties

Other logarithm properties:

1 ln bx = ln b + ln x

b

2 ln x = ln b ln x

Properties Other logarithm properties: 1 ln bx = ln b + ln x b 2 ln

Properties

Other logarithm properties:

1 ln bx = ln b + ln x

2

b

ln x = ln b ln x

1

3 ln x = ln x

Other logarithm properties: 1 ln bx = ln b + ln x 2 b ln x

Properties

Other logarithm properties:

1 ln bx = ln b + ln x

2

b

ln x = ln b ln x

3 ln x = ln x

4 ln x r = rln x, r Q

1

bx = ln b + ln x 2 b ln x = ln b − ln

Properties

Other logarithm properties:

1 ln bx = ln b + ln x

2

b

ln x = ln b ln x

3 ln x = ln x

4 ln x r = rln x, r Q

1

All of these properties can be generalized for log b x.

x = − ln x 4 ln x r = r ln x , r ∈

Examples

1

What is x dx?

Examples 1 What is x d x ?

Examples

1

What is x dx?ln |x| + c

Examples 1 What is x d x ?ln | x | + c

Examples

1

What is x dx?ln |x| + c

Example

Evaluate 1 x x 2 + 1 dx −1
Evaluate
1
x
x 2 + 1 dx
−1

Examples

1

What is x dx?ln |x| + c

Example

Evaluate 1 x x 2 + 1 dx −1
Evaluate
1
x
x 2 + 1 dx
−1

u =

Examples 1 What is x d x ?ln | x | + c Example Evaluate 1

Examples

1

What is x dx?ln |x| + c

Example

Evaluate 1 x x 2 + 1 dx −1
Evaluate
1
x
x 2 + 1 dx
−1

u = x 2 + 1

Examples 1 What is x d x ?ln | x | + c Example Evaluate 1

Examples

1

What is x dx?ln |x| + c

Example

Evaluate 1 x x 2 + 1 dx −1
Evaluate
1
x
x 2 + 1 dx
−1

u = x 2 + 1

du =

Examples 1 What is x d x ?ln | x | + c Example Evaluate 1

Examples

1

What is x dx?ln |x| + c

Example

Evaluate 1 x x 2 + 1 dx −1
Evaluate
1
x
x 2 + 1 dx
−1

u = x 2 + 1

du = 2x dx

1 What is x d x ?ln | x | + c Example Evaluate 1 x

Examples

1

What is x dx?ln |x| + c

Example

Evaluate 1 x x 2 + 1 dx −1 1 x=1 du u = x
Evaluate
1
x
x 2 + 1 dx
−1
1
x=1
du
u = x 2 + 1
2
u
x=−1
du = 2x dx
2 1 du = x dx

Examples

1

What is x dx?ln |x| + c

Example

Evaluate 1 x x 2 + 1 dx −1 1 x=1 du u = x
Evaluate
1
x
x 2 + 1 dx
−1
1
x=1
du
u = x 2 + 1
2
u
x=−1
1
x=1
du = 2x dx
=
2 ln |u|
x=−1
2 1 du = x dx

Examples

1

What is x dx?ln |x| + c

Example

Evaluate 1 x x 2 + 1 dx −1
Evaluate
1
x
x 2 + 1 dx
−1

u = x 2 + 1

du = 2x dx

2 1 du = x dx

=

1 x=1 du 2 u x=−1 1 x=1 = 2 ln |u| x=−1 1 1
1
x=1
du
2
u
x=−1
1
x=1
=
2 ln |u|
x=−1
1
1 2 ln |x 2 + 1|
−1 =

Examples

1

What is x dx?ln |x| + c

Example

Evaluate 1 x x 2 + 1 dx −1
Evaluate
1
x
x 2 + 1 dx
−1

u = x 2 + 1

du = 2x dx

2 1 du = x dx

=

1 x=1 du 2 u x=−1 1 x=1 = 2 ln |u| x=−1 1 1
1
x=1
du
2
u
x=−1
1
x=1
=
2 ln |u|
x=−1
1
1 2 ln |x 2 + 1|
−1 = 0

Note

Note: the fact that we have a symmetric interval and we get 0 for the value of the integral tells us what?

Note Note: the fact that we have a symmetric interval and we get 0 for the

Note

Note: the fact that we have a symmetric interval and we get 0 for the value of the integral tells us what?

The function is odd.

the fact that we have a symmetric interval and we get 0 for the value of

Exponentials

Let’s turn our attention to exponentials. If we consider f(x) = e x , what does the graph look like?

Let’s turn our attention to exponentials. If we consider f ( x ) = e x

Exponentials

Let’s turn our attention to exponentials. If we consider f(x) = e x , what does the graph look like?

Let’s turn our attention to exponentials. If we consider f ( x ) = e x

Exponentials

Let’s turn our attention to exponentials. If we consider f(x) = e x , what does the graph look like?

f ( x ) = e x , what does the graph look like? We know

We know lim

x e x = and lim

x→−e x = 0.

x , what does the graph look like? We know lim x → ∞ e x

Exponentials

What is

d

dx

e x ?

Exponentials What is d d x e x ?

Exponentials

What is

d

dx

e x ? e x

Exponentials What is d d x e x ? e x

Exponentials

What is

d

dx

e x ? e x

e x > 0 x R, so the function is

Exponentials What is d d x e x ? e x e x > 0 ∀

Exponentials

What is

d

dx

e x ? e x

e x > 0 x R, so the function is increasing everywhere.

What is d d x e x ? e x e x > 0 ∀ x

Exponentials

What is

d

dx

e x ? e x

e x > 0 x R, so the function is increasing everywhere.

And, since

2 e x =

dx

d

2

? e x e x > 0 ∀ x ∈ R , so the function is

Exponentials

What is

d

dx

e x ? e x

e x > 0 x R, so the function is increasing everywhere.

And, since

2 e x = e x , we know that the function is concave up.

dx

d

2

function is increasing everywhere. And, since 2 e x = e x , we know that

Exponentials

By this same logic, we have the following:

e x dx = e x + c

Exponentials By this same logic, we have the following: e x d x = e x

Exponentials

By this same logic, we have the following:

and in general,

e x dx = e x + c

e u du = e u + c

with the difference being that u is a function of x and would require substitution to integrate.

u d u = e u + c with the difference being that u is a

Derivative of e x

Who can tell me why the derivative of e x is e x ?

Derivative of e x Who can tell me why the derivative of e x is e

Derivative of e x

Who can tell me why the derivative of e x is e x ?

When in doubt, we can go back to the limit of the difference quotient.

d

dx e x = lim

h0

e x+h e x

h

we can go back to the limit of the difference quotient. d d x e x

Derivative of e x

Who can tell me why the derivative of e x is e x ?

When in doubt, we can go back to the limit of the difference quotient.

d

dx e x = lim

h0

e x+h e x

h

= e x lim

h0

e h 1

h

difference quotient. d d x e x = lim h → 0 e x + h

Derivative of e x

Now, we expect the expression we are taking the limit of to equal 1 so that we end up with just e x .

of e x Now, we expect the expression we are taking the limit of to equal

Derivative of e x

Now, we expect the expression we are taking the limit of to equal 1 so that we end up with just e x . So let’s pull this part out for the moment.

e h 1

h

= 1

of to equal 1 so that we end up with just e x . So let’s

Derivative of e x

Now, we expect the expression we are taking the limit of to equal 1 so that we end up with just e x . So let’s pull this part out for the moment.

e h 1

h

= 1

h = e h 1

we end up with just e x . So let’s pull this part out for the

Derivative of e x

Now, we expect the expression we are taking the limit of to equal 1 so that we end up with just e x . So let’s pull this part out for the moment.

e h 1

h

h

h

= 1

= e h 1 + 1 = e h

just e x . So let’s pull this part out for the moment. e h −

Derivative of e x

Now, we expect the expression we are taking the limit of to equal 1 so that we end up with just e x . So let’s pull this part out for the moment.

e h 1

h

h

h

= 1

= e h 1 + 1 = e h

Now we will bring the limit back in.

lim

h0 h + 1 = e h

1 h h h = 1 = e h − 1 + 1 = e h

Derivative of e x

Now, we expect the expression we are taking the limit of to equal 1 so that we end up with just e x . So let’s pull this part out for the moment.

e h 1

h

h

h

= 1

= e h 1 + 1 = e h

Now we will bring the limit back in.

lim

h0 h + 1 = e h

1 = e 0 1 = 1

This gives us that the expression we wanted to be 1 is 1 and we get the desired result.

h ⇒ 1 = e 0 ⇒ 1 = 1 This gives us that the expression

Derivative of Exponentials

In general,

d dx a x =

Derivative of Exponentials In general, d d x a x =

Derivative of Exponentials

d

In general, dx a x = a x ln a. Where does this come from?

Derivative of Exponentials d In general, d x a x = a x ln a .

Derivative of Exponentials

d

In general, dx a x = a x ln a. Where does this come from?

y = a x ln y = ln a x

d In general, d x a x = a x ln a . Where does this

Derivative of Exponentials

d

In general, dx a x = a x ln a. Where does this come from?

y = a x ln y = ln a x ln y = x ln a

d x a x = a x ln a . Where does this come from? y

Derivative of Exponentials

d

In general, dx a x = a x ln a. Where does this come from?

y = a x

ln y = ln a x

ln y = x ln a 1 dy

= ln a

y dx

= a x ln a . Where does this come from? y = a x ln

Derivative of Exponentials

d

In general, dx a x = a x ln a. Where does this come from?

y = a x

ln y = ln a x

ln y = x ln a 1 dy

= ln a

y dx

dy

dx

= y ln a

a . Where does this come from? y = a x ln y = ln a

Derivative of Exponentials

d

In general, dx a x = a x ln a. Where does this come from?

y = a x

ln y = ln a x

ln y = x ln a 1 dy

= ln a

y dx

dy

dx

=

= y ln a

a x ln a

a x ln y = ln a x ln y = x ln a 1 d

Derivative of Exponentials

d

In general, dx a x = a x ln a. Where does this come from?

This leads us to

y = a x

ln y = ln a x

ln y = x ln a 1 dy

= ln a

y dx

dy

dx

= y ln a

= a x ln a u d a dx a u = a u (ln
= a x ln
a
u
d
a
dx a u = a u (ln a) du
and a u du =
dx
ln a + c.

Properties

Some properties of exponential:

1 e x 1 +x 2

= e x 1 · e x 2

Properties Some properties of exponential: 1 e x 1 + x 2 = e x 1

Properties

Some properties of exponential:

1 e x 1 +x 2

2 e x =

= e x 1 · e x 2

1

e x

Some properties of exponential: 1 e x 1 + x 2 2 e − x =

Properties

Some properties of exponential:

1 e x 1 +x 2

= e x 1 · e x 2

2 e x =

e

x

1

3 e x 2

1

e x

= e x 1 x 2

1 + x 2 = e x 1 · e x 2 2 e − x

Properties

Some properties of exponential:

1 e x 1 +x 2

2 e x =

e

x

1

3 e x 2

=

= e x 1 · e x 2

1

e x

e x 1 x 2

4 (e x 1 ) r = e rx 1 , for r Q

= = e x 1 · e x 2 1 e x e x 1 −

Properties

Some properties of exponential:

1 e x 1 +x 2

2 e x =

e

x

1

3 e x 2

=

= e x 1 · e x 2

1

e x

e x 1 x 2

4 (e x 1 ) r = e rx 1 , for r Q

5 x = e lnx

· e x 2 1 e x e x 1 − x 2 4 ( e

Properties

Some properties of exponential:

1 e x 1 +x 2

2 e x =

e

x

1

3 e x 2

=

= e x 1 · e x 2

1

e x

e x 1 x 2

4 (e x 1 ) r = e rx 1 , for r Q

5 x = e lnx

6 x = ln e x

e x e x 1 − x 2 4 ( e x 1 ) r =

Derivatives

Find the derivative of the following:

Example

f(x) = a x + x a

Derivatives Find the derivative of the following: Example f ( x ) = a x +

Derivatives

Find the derivative of the following:

Example

f(x) = a x + x a

f (x) = ln a · a x + ax a1

the derivative of the following: Example f ( x ) = a x + x a

Derivatives

Find the derivative of the following:

Example

f(x) = a x + x a

f (x) = ln a · a x + ax a1

f ( x ) = a x + x a f ( x ) = ln

Example g(x) = sin(e x )

f ( x ) = a x + x a f ( x ) = ln
f ( x ) = a x + x a f ( x ) = ln

Derivatives

Find the derivative of the following:

Example

f(x) = a x + x a

f (x) = ln a · a x + ax a1

+ x a f ( x ) = ln a · a x + ax a

Example g(x) = sin(e x )

g (x) = e x cos(e x )

( x ) = ln a · a x + ax a − 1 Example g

Derivatives

Find the derivative of the following:

Example

f(x) = a x + x a

f (x) = ln a · a x + ax a1

Example g(x) = sin(e x ) g (x) = e x cos(e x ) Example
Example
g(x) = sin(e x )
g (x) = e x cos(e x )
Example
log x
y =
1+log x

Derivatives

Find the derivative of the following:

Example

f(x) = a x + x a

f (x) = ln a · a x + ax a1

Example g(x) = sin(e x ) g (x) = e x cos(e x ) Example
Example
g(x) = sin(e x )
g (x) = e x cos(e x )
Example
1
1
(1+log x)
log x
xln(10) −log x
xln(10)
y =
x y =
1+log
(1+log x) 2

Derivatives

Find the derivative of the following:

Example

f(x) = a x + x a

f (x) = ln a · a x + ax a1

Example g(x) = sin(e x ) g (x) = e x cos(e x ) Example
Example
g(x) = sin(e x )
g (x) = e x cos(e x )
Example
1
1
(1+log x)
log x
xln(10) −log x
xln(10)
1
y =
x y =
1+log
(1+log x) 2
= x ln(10)(1+log x) 2

Derivatives

Find the derivative of the following:

Example

f(x) = a x + x a

f (x) = ln a · a x + ax a1

Example g(x) = sin(e x ) g (x) = e x cos(e x ) Example
Example
g(x) = sin(e x )
g (x) = e x cos(e x )
Example
1
1
(1+log x)
log x
xln(10) −log x
xln(10)
1
y =
x y =
1+log
(1+log x) 2
= x ln(10)(1+log x) 2

Example

y = log (x 2 + 1)

−log x xln(10) 1 y = x y = 1+log (1+log x) 2 = x ln(10)(1+log

Derivatives

Find the derivative of the following:

Example

f(x) = a x + x a

f (x) = ln a · a x + ax a1

Example g(x) = sin(e x ) g (x) = e x cos(e x ) Example
Example
g(x) = sin(e x )
g (x) = e x cos(e x )
Example
1
1
(1+log x)
log x
xln(10) −log x
xln(10)
1
y =
x y =
1+log
(1+log x) 2
= x ln(10)(1+log x) 2
Example
2x
y = log (x 2 + 1)
y =
(ln 10)(x 2 +1)

Another Example

Example log x dx x
Example
log x
dx
x

Another Example

Example log x dx x
Example
log x
dx
x

We first want to apply the “change of base” rule.

log x =

ln x

ln 10

and the reason is because we know how to take the antiderivative when we rewrite.

base” rule. log x = l n x ln 10 and the reason is because we

Another Example

Example log x dx x
Example
log x
dx
x

We first want to apply the “change of base” rule.

log x =

ln x

ln 10

and the reason is because we know how to take the antiderivative when we rewrite.

log x

x

dx

=

1 10 ln x dx ln x
1
10 ln x
dx
ln
x

Another Example

We now apply the substitution rule.

1

u = ln x du = x dx

Another Example We now apply the substitution rule. 1 u = ln x ⇒ d u

Another Example

We now apply the substitution rule.

So now we have

1

u = ln x du = x dx

1

10 u du

ln

Example We now apply the substitution rule. So now we have 1 u = ln x

Another Example

We now apply the substitution rule.

So now we have

1

u = ln x du = x dx

1

10 u du

ln

= (ln x) 2

2ln 10 + c

rule. So now we have 1 u = ln x ⇒ d u = x d